Managing your intellectual property assets - Shane, Scott Andrew 1964- (Business Expert Press, 2008)
Why you need intellectual property protection -- What is patentable -- The parts of a patent -- Using a patent -- Should you patent -- Secrecy -- Copyrights -- Trademarks -- Conclusion
Includes bibliographical references (p. 51-58) and index
Keywords: Intellectual property / Management